PENDAMPINGAN DAN PELATIHAN PENINGKATAN KREATIVITAS ANAK PUTUS SEKOLAH BERBASIS PEMBELAJARAN KELAS MOTIVASI DAN NON AKADEMIK KP. TUNANGAN DESA MANGUNJAYA KEC. CUGENANG KAB. CIANJUR (Jurnal Mitra Masyarakat (JMM), 2023)
Introduction: Development of human resources, especially youth is one way for a developing country to promote development in all aspects of the field. SD show 38 thousand, SMP reaches 29. 793 students, around 5.000 students drop out of school. The area with the most dropout is Cugenang sub-district with 532 students. The purpose of this community service is to provide assistance and training to increase the creativity of Kp. Mangunjaya Village Fiance, Kec. Cugenang District Cianjur. Method: the method used is Participatory Action Research (PAR). PAR is a participatory research and advocacy activity among people in a community that encourages transformative action and involving the community, in this case youth (children dropping out of school) to become morereactive people. The sample used the total sampling method, with a total number participants 37. of Reserch Results: The activity took place not only to strengthen the contribution of thr STIKes Permata Nusantara team, which collaborates with P2WKSS in providing motivation to continue school but also being taught directly the practice of making a bouquet of snack, this can increase economic income and family welfare which in turn can improve health status family. Conclusion: The empowerment carried out on the target group (dropouts) through the Community service program in collaboration with P2WKSS has been carried out in accordance with the seven (7) stages of empowerment.